SUMBERDAYA BATUBARA KAWASAN BLOK PT. TEUNOM RESOURCES, KAB. ACEH BARAT, PROPINSI NANGGROE ACEH DARUSSALAM - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Recognissances was carried out in blocks of coal PT. Teunom Resources, which all belong to Meulaboh area, West Aceh Regency, the Province of Nangrroe Aceh Darussalam.The area of Meulaboh geologically belong to Plio-Pliestocene age Tutut Formation in land and maish environment deposition. The litology consist of conglomerate, sandstone, claystone and lignite. The basin of this Formation deposition is well known as “ Meulaboh Embayment “.The compiled reference some previous exploration result on the thickness of coal seams in Meulaboh ranging some centimeters to 8 (eight) meters and morever the calorivic value ranging 3900 – 5100 cal/gr. The result of recognissance in the surveyed area appears that the observed coal seams occurs as intercalation and lenses of some centimeter to 80 centimeters of thickness where the strike of layer trending northwest – southeast and dipping ranging 4º - 5º. Among the above mentioned block, the number of seam outcrops occur much more in block PT. Teunom Resources. The reserve restricted to the 3 layers of 80 centimeters dippingt less 5º is roughly estimated 2.633.133 tons.The quality of coal as analyzed by the Directorate of Minerals Resources in Bandung appears as follow: Total Sulphur 0.19% - 0.35% adb; Ash 4.33% - 7.39% adb; Fix Carbon 33.00% - 39.27% adb; Volatile Matter 47.01% - 54.17% adb; Moisture 8.19% - 8.97% adb; Total Moisture 43.22% - 47.23% ar; and Free Moisture 38.15% - 42.03% ar.